Analisis Keterampilan Bertanya Guru Ekonomi Pada Kelas VII Di SMP Kartika Ambon - Aminah Rehalat; zuhria nurul 'ainy (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to identify and analyze the teacher's questioning skills which consist of 2 parts, namely basic questioning skills and advanced questioning skills. The variable used in this study is a single variable, namely questioning skills. This research is a qualitative descriptive research that is presenting data for each variable studied and performing calculations to answer the problem formulation. The research method used to collect data is observation, interviews and documents. Observations and interviews were used to collect data regarding the teacher's questioning skills while documents were used to collect data regarding the general description of the research location. The data collection process was carried out by connecting the study material with field research, where the author was assisted by 1 colleague, namely an economics teacher. The results of the study showed that the class VII_(1) economics teacher at Kartika Ambon Middle School had carried out questioning skills well. This can be seen from the 2 indicators and 8 sub-indicators that must be mastered by a teacher where the first indicator, namely basic questioning skills, is in good qualifications and the second indicator, namely advanced questioning skills, is in fairly good qualifications. Thus, the skills of asking teachers at these educational institutions are quite good.